The Role of the P1 Latency in Auditory and Speech Performance Evaluation in Cochlear Implanted Children - Shan Xiong; Liwei Jiang; Yu Wang; Tao Pan; Furong Ma (Neural Plasticity)
Auditory deprivation affects normal age-related changes in the central auditory maturation. Cochlear implants (CIs) have already become the best treatment strategy for severe to profound hearing impairment. However, it is still hard to evaluate the speech-language outcomes of the pediatric CI recipients because of hearing-impaired children with limited speech-language abilities. The cortical auditory evoked potential (CAEP) provides a window into the development of the auditory cortical pathways. This preliminary study is aimed at assessing electrophysical characteristics of P1-N1 of electrically CAEP in children with CIs and at exploring whether these changes could be accounted for in auditory and speech outcomes of these patients. CAEP responses were recorded in 48 children with CIs in response to electrical stimulus to determine the presence of the P1-N1 response. Speech perception and speech intelligibility of the implanted children were further evaluated with the categories of auditory performance (CAP) test and speech intelligibility rating (SIR) test, respectively, to explore the relationship between the latency of P1-N1 and auditory and speech performance. This study found that P1 and N1 of the intracochlear CAEP were reliably evoked in children fitted with CIs and that the latency of the P1 as opposed to that of N1 was negative in relation to the wearing time of the cochlear implant. Moreover, the latency of the P1 produced significantly negative scores in both CAP and SIR tests, which indicates that P1 latency may be reflective of the auditory performance and speech intelligibility of pediatric CI recipients. These results suggest that the latency of P1 could be used for the objective assessment of auditory and speech function evaluation in cochlear-implanted children, which would be helpful in clinical decision-making regarding intervention for young hearing-impaired children.